Faktor Dominan yang Berhubungan dengan Kekurangan Energi Kronis pada Ibu Hamil di Tlogosari, Bondowoso: Dominant Factors Associated with Chronic Energy Deficiency in Pregnant Women in Tlogosari, Bondowoso - Asdam, Wulan Syarani; Puspikawati, Septa Indra; Sari, Jayanti Dian Eka; Bakomora, Brenda (Amerta Nutrition, 2025)
Background: The high prevalence of Chronic Energy Deficiency (CED) in Bondowoso Regency, affecting 16.4% of women of reproductive age and 17.67% of pregnant women in 2023, indicates the need for further analysis of its contributing factors. CED increases the risk of maternal and infant mortality, as well as adverse cases such as low birth weight and stunting. Objectives: This study aimed to analyze suspected contributing factors and determine the most dominant factor associated with Chronic Energy Deficiency (CED) among pregnant women in the working area of Tlogosari Health Center, Bondowoso Regency, East Java Province, Indonesia. Methods: This study used a case-control design, involving 96 pregnant women (48 with CED and 48 without CED) in Tlogosari Subdistrict. The analyzed variables included age, education, history of infectious diseases, parity, pregnancy spacing, dietary patterns, nutritional knowledge, and socioeconomic status. Data were collected through questionnaire and analyzed using descriptive statistics, chi-square tests, odds ratios, and logistic regression. The sample was selected using simple random sampling. Results: The logistic regression test results indicated that nutritional knowledge (OR=7.509; 95%CI=1.948-28.954; p-value=0.003) and history of infectious diseases (OR=0.091; 95%CI=0.023-0.367; p-value=0.001) were significantly associated with Chronic Energy Deficiency (CED) among pregnant women in the working area of Tlogosari Community Health Center. Conclusions: Poor nutritional knowledge and a history of infectious diseases were significantly associated with CED, with nutritional knowledge emerging as the most dominant factor. Improving personal hygiene practices and enhancing nutritional education during pregnancy are essential to reduce the risk of CED.